Effect of different BAP concentration on shoot multiplication from shoot tip explant of F1 hybrid brinjal (Solanum melongena) - Mohamad Nabawi, Muhamad Nasrul Hazli (2013)
Solanummelongena isone of the important vegetables in this world where its estimated world production is reaching 47 million tons in 2011. This vegetable is also indicated for the treatment of several diseases, including diabetes, arthritis, asthma and bronchitis. An F1 hybrid cultivar of this species cannot be propagated using seeds because it cannot maintain the true to typeness at the second filial generation (F2 generation). Therefore an alternative approach to maintain true to typness and uniformity of the propagule is through propagation by asexual means. Since, in vitro culture can mass produce propagules within a shorter period of time this approach is justified as a means to propagate S.melongenaF1 hybrid plant. Therefore an experiment was carried out to study the effect of different BAP concentration on shoot multiplication from shoot tip explants of F1 hybrid brinjal. Five BAP treatments wereused in this experiment which were 0.0, 0.5, 1.0, 2.5, and 5.0 mg/L. The experiment was conducted using a completely randomized design (CRD) with 12 replications per treatment. One explant was used for each treatment per replication. All the explants were cultured on half strength MS medium with the different BAP treatments. Data collections were taken for 6 weeks based on the percentage of explants regenerating shoot and the number of shoot formed per explant. It was observed thatthe shoot tip explants cultured on medium containing 2.5 mg/L BAP had the highest percentage of explants forming new shoots after 6 weeks of culture compared to other treatments. Analysis of variance also showed there was no significant difference on mean number of shoot per explant between the BAP treatments including the control (0.0 mg/L BAP).